The AI-driven strategic enhancement scenario building for ABC company's english operations - Montojo, Eunica M.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2025)
The project was designated to develop sustainable and innovative approaches aimed at optimizing IT service management (ITSM) while simultaneously minimizing environmental impact. This initiative was particularly significant in addressing the inefficiencies and resource-intensive nature of traditional ITSM practices, which often led to increased carbon footprints. By promoting green IT, the project sought to achieve not only cost savings but also regulatory compliance, thereby aligning with contemporary environmental standards.
Anticipated outcomes of the project included measurable reductions in energy consumption and carbon footprint, successful implementation of AI/ML solutions that enhanced operational efficiency, and improved internal communication that led to higher service satisfaction among stakeholders. The project was structured into four distinct phases, encompassing research, development, testing, and training.
Key stakeholders involved in this initiative included top management, development and operations teams, and functional managers, all of whom played a crucial role in ensuring the project's success and alignment with organizational goals. Their engagement and support were vital in navigating the challenges and opportunities that arose throughout the project lifecycle.
In partial fulfillment of the requirements of the Master of Technology Management Program
Thesis
Keywords: Artificial intelligence -- Environmental aspects; Machine learning -- Industrial applications; Energy consumption -- Management; Project management